Usos e apropriações do lugar sagrado nas especificidades das festas/espetáculos na Capela da Saudade em Uberlândia (MG) e na Igreja da Madeleine em Paris (França) - Silva, Rene Gonçalves Serafim (2018)
This work seeks to understand the spectacularization of the sacred place from festivities. We realize a comparative analysis between the Capela da Saudade in Uberlândia, city of Minas Gerais state, and the Church of Madeleine in Paris, France. In this research, we approach key concepts to the work, such as place, parties, sacred and profane, spectacularization, being these concepts the theoretical and methodological purpose. In addition, we propose a system to understand this spectacularization from the notion of “place-spectacle”, presenting two conceptions: the permanent place-spectacle and the transitory place-spectacle. The methodology of the research was based on the bibliographical collection and discussion about the topic, and then the field work on both places. After that, we have made our comparative analysis. The results indicated that the spectacularization of the sacred place takes place because of the social and spatial changes and, specially, from the new ways and relations that the party promotes in those places. They aim to make a party profitable and promote itself. The recreated sacred-profane party in Paris or in Brazil, those places allow us to think in their spaces such a place-spectacle. The great events make it potent, resulting in a party’s appropriation.